merancang aplikasi penjualan hid Rancang Bangun Aplikasi Penjualan Hidroponik Berbasis Website Desa Rengel Kabupaten Tuban - M. Isnainur Hidyatullah; Ilyas Nuryasin; Gita Indah Marthasari (Universitas Muhammadiyah Malang, 2023)
Plant cultivation without soil media (hydroponics) is a method of planting using water-based planting media that is nutritious, thus having the advantage of maintaining cleanliness because it does not use soil media. Usually, soil serves as a provider of nutrients (nutrients) and support, but in hydroponics, the role of soil as a provider of nutrients is obtained from the AB mix nutrient solution and other planting media such as rockwool or cocopeat (coconut fiber processing) as support. Vegetable farmers often use this method to produce products with guaranteed quantity and quality, especially vegetables that are safe for consumption because they do not use pesticides. However, hydroponic farmers face the main problem of lack of access to buyers, so they have to sell their products at a low price to intermediaries or traders. Another problem is that many farmers do not have their own transportation vehicles, so they have to spend extra money to rent vehicles. To overcome these problems, a hydroponic application design is needed which aims to facilitate communication between farmers and buyers and enable farmers to sell their harvest at a more reasonable price without the interference of intermediaries or traders. This application is also equipped with a transporter feature whose cost will be charged to the buyer. This application is created using the RAD (Rapid Application Development) method and tested using the Blackbox Testing method and a sample questionnaire of 5 users. The results of this research show that this hydroponic application can facilitate communication between farmers and buyers and help farmers sell their harvest at a reasonable price.